2011
DOI: 10.1007/s10266-011-0022-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enamel matrix protein on gingival tissue thickness in vivo

Abstract: The enamel matrix derivative (EMD) has been used extensively as an adjunct to root coverage procedures to achieve periodontal regeneration. However, its effect on gingival tissues has not been elucidated. The aim of this investigation was to evaluate histometrically the change in gingival soft tissue thickness around dehiscence-type defects treated with EMD. Five adult female beagle dogs were used. Buccal osseous dehiscences were surgically created on the maxillary canines and the second and fourth premolars. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Recent studies [47][48][49] have reported that biomimicry agent (such as enamel matrix derivative [EMD]) proteins promote tissue repair and regeneration at defected sites. These studies [47][48][49] revealed that EMD proteins exhibit the potential to enhance the healing of standardized epithelial wounds, induce cementogenesis, and increase the thickness of gingival tissues. It is therefore hypothesized that treatment of GR defects using ADM with adjunct EMD therapy may enhance gingival tissue thickness and yield positive outcomes in terms of root coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [47][48][49] have reported that biomimicry agent (such as enamel matrix derivative [EMD]) proteins promote tissue repair and regeneration at defected sites. These studies [47][48][49] revealed that EMD proteins exhibit the potential to enhance the healing of standardized epithelial wounds, induce cementogenesis, and increase the thickness of gingival tissues. It is therefore hypothesized that treatment of GR defects using ADM with adjunct EMD therapy may enhance gingival tissue thickness and yield positive outcomes in terms of root coverage.…”
Section: Discussionmentioning
confidence: 99%
“…It is an effective agent for stimulating periodontal regeneration with formation of a new acellular extrinsic fiber cementum, which firmly attaches to the denuded root surface [22,23]. Moreover, it has recently been demonstrated that EMD has a positive influence on the increase in gingival thickness in dehiscence-type defects in dogs [24]. These results might propose a new rationale for the increased predictability of CAF in achieving complete root coverage when EMD and/or PADM is used adjunctively.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, application of Emdogain during coronally positioned flap procedures for correction of gingival recession resulted in an increase in the width and density of the keratinized gingiva compared with the control treatment. Emdogain also stimulated an increase in gingival tissue thickness in dehiscence‐type defects in Beagle dogs and increased the speed of early connective tissue healing around dental implants . These clinical observations suggest that Emdogain may have direct effects on gingival healing and gingival fibroblasts.…”
Section: In Vitro Models Of Soft‐tissue Wound Healingmentioning
confidence: 68%